Družinska (ne)harmonija ob računalniških zaslonih - Oblak, Tanja (Družboslovne razprave, 2009)
The main characteristic of communication technologies is that they are ever more present in our homes. As a consequence, computer technology plays an important role in the process of building our private sphere. At the same time, these technologies are the subject of increasing domestication. This domestication process includes an analysis of the causes, motives and patterns of adopting communication technologies. Interviews with parents and their children in various Slovenian families have shown that the Internet is considered the most important dimension of the computer as a modern domestic appliance. The possibility of logging on to the Web has substantially contributed to the spread of the communicational and social dimensions of computer technology. Although at the beginning the computer was primarily considered "a business device" or "a toy", today new meanings are being attributed to it: the computer is not only "an investment for the future" or "an extension of parental responsibilities". It also plays several controversial roles such as being "an intruder" or "a destroyer of personal relationships" on one hand, or "a comforter" and "a multi-purpose tool for every occasion" on the other, depending on the generation the user belongs to. While young people perceive computer technology as a bridge between various structures of everyday life, their parents often consider the same technology as a major factor in the disintegration of family life.
Keywords: Communication technology; Komunikacijska tehnologija; Informacijska tehnologija; Information technology; Družina; Family; Privacy; Zasebnost; Generacije; Generations; osebni računalniki; medgeneracijski odnosi